2013
DOI: 10.1080/08927014.2013.834332
|View full text |Cite
|
Sign up to set email alerts
|

Anin vivomethod for measuring the adsorption of plasma proteins to titanium in humans

Abstract: A novel method of collecting in vivo plasma proteins of humans from osteotomies prepared during insertion of an oral implant is described. A rod containing a collecting portion with a predetermined surface is introduced into the osteomy, removed, and transferred for enzyme-linked immunosorbent assay analysis. Two experiments were used to examine the feasibility of the method. In the first, titanium (Ti) rods with different roughness were exposed for 10 min to the blood. Blasted and acid-etched surfaces adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…However, the higher protein adsorption rate onto Plasmapore‐coated Ti surface compared to smoother surface geometries in our study correspond to the study of Kohavi et al . In their experiments they found four times higher protein adsorption for sand‐blasted Ti surfaces compared to machined surfaces.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the higher protein adsorption rate onto Plasmapore‐coated Ti surface compared to smoother surface geometries in our study correspond to the study of Kohavi et al . In their experiments they found four times higher protein adsorption for sand‐blasted Ti surfaces compared to machined surfaces.…”
Section: Discussionsupporting
confidence: 91%
“…Practically nothing is known about the biological effects and interactions between the other adsorbed proteins orchestrating implant integration in cementless total hip replacement. This is in contrast to other experimental studies emphasizing the relevance of other proteins such as fibronectin (Fn), fibrinogen or thrombin as a molecular glue, anchoring osteoblasts to the implant . Some in vitro data indicate that fibronectin showed excellent adsorption on titanium surfaces even at low concentrations in vitro .…”
Section: Discussionmentioning
confidence: 65%
“…Nagassa et al observed that the degree of BSA adsorption in vitro on a surface with nanometer‐scale structural features was higher than that on a similar but smooth surface . Kohavi et al also observed that the in vivo adsorption of human plasma proteins on an acid‐etched rough surface (Ra = approximately 200 nm) was higher than that on a machined smooth surface (Ra = approximately 20 nm) . After the AH treatment, nanometer‐ and/or micrometer‐scale structural features were formed on the surface of the treated Ti sample, as shown in Figures and .…”
Section: Discussionmentioning
confidence: 96%
“…29 Kohavi et al also observed that the in vivo adsorption of human plasma proteins on an acidetched rough surface (Ra 5 approximately 200 nm) was higher than that on a machined smooth surface (Ra 5 approximately 20 nm). 30 After the AH treatment, nanometer-and/or micrometer-scale structural features were formed on the surface of the treated Ti sample, as shown in Figures 1 and 2. However, the original microscaled surface outline remained intact [ Figure 1(A)], and the surface roughness of the AHtreated was only slightly higher, as shown in Figure 2(A).…”
Section: Discussionmentioning
confidence: 98%
“…[41] α-Amylase formed clusters or aggregates when adsorbed onto the surface of interlayer like IgG and fibrinogen, resulting in differences in layer thickness and morphology. [42] (Fig. 3 and 4).…”
Section: Accepted Manuscriptmentioning
confidence: 89%